Experimental model of the aerodynamic drag coefficient in alpine skiing - Barelle, C.; Ruby, A.; Tavernier, M. (Journal of Applied Biomechanics, 2004)
Aerodynamic properties are one of the factors that determine speed performance in Alpine skiing. Many studies have examined the consequences of this factor in downhill skiing, and the impact of postural modifications on speed is now well established. To date, only wind tunnel tests have enabled one to measure aerodynamic drag values (a major component of the aerodynamic force in Alpine skiing). Yet such tests are incompatible with the constraints of a regular and accurate follow-up of training programs. The present study proposes an experimental model that permits one to determine a skier`s aerodynamic drag coefficient (SCx) based on posture. Experimental SCx measurements made in a wind tunnel are matched with the skier`s postural parameters. The accuracy of the model was determined by comparing calculated drag values with measurements observed in a wind tunnel for different postures. For postures corresponding to an optimal aerodynamic penetration (speed position), the uncertainty was 13%. Although this model does not permit an accurate comparison between two skiers, it does satisfactorily account for variations observed in the aerodynamic drag of the same skier in different postures. During Alpine ski training sessions and races, this model may help coaches assess the gain or loss in time induced by modifications in aerodynamic drag corresponding to different postures. It may also be used in other sports to help determine whether the aerodynamic force has a significant impact on performance.